Down the bright stream : the prehistory of Woodcock Corner and the Tregurra Valley, Cornwall - Taylor, Sean R., (Archaeopress Archaeology, 2022)
This volume reports on a series of fieldwork projects carried out in the Tregurra Valley, to the east of Truro, Cornwall between 2009-2015. The fieldwork led to the identification of a large number of pits and hearths across the site, the majority of which that have proved dateable spanning the Early Neolithic to the end of the Early Bronze Age.